Microchip Nd:YAG and Nd:YVO4 Lasers Pumped by VHG Wavelength-Stabilized Laser Diode - T. Saiki; A. Tatebayashi (International Journal of Optics)
We adopted a single-mode, single-wavelength volume holographic grating (VHG) wavelength-stabilized wavelength laser diode (LD) as a pumping LD for an end-pumped microchip Nd:YAG and Nd:YVO4 lasers we developed during CW and pulse operations. Higher optical-optical and slope efficiencies during CW operation have been obtained than when using a VHG LD experimentally. Output laser power is insensitive to the temperature of the LD when using a wavelength-stabilized LD and can remain stable and almost constant until the temperature of LD increases up to 40°C. The improved optical-optical conversion efficiency of 58% for the Nd:YVO4 laser has been obtained and calculated the output laser power during CW operation and compared it with the experimental results. We found that the output laser power of the Nd:YVO4 laser using the VHG wavelength-stabilized LD was more than twice as high as that using an LD without VHG. When the ambient temperature increases, the difference in output laser power should be large. In the future, a low-cost end-pumped microchip laser that does not require a temperature control should be developed.